Dendritic cells loaded with exosomes derived from cancer stem cell‐enriched spheroids as a potential immunotherapeutic option. Issue 7 (25th February 2021) - Naseri, Marzieh; Zöller, Margot; Hadjati, Jamshid; Ghods, Roya; Ranaei Pirmardan, Ehsan; Kiani, Jafar; Eini, Leila; Bozorgmehr, Mahmood; Madjd, Zahra
Abstract: Cancer stem cells (CSCs) are responsible for therapeutic resistance and recurrence in colorectal cancer. Despite advances in immunotherapy, the inability to specifically eradicate CSCs has led to treatment failure. Hence, identification of appropriate antigen sources is a major challenge in designing dendritic cell (DC)‐based therapeutic strategies against CSCs. Here, in an in vitro model using the HT‐29 colon cancer cell line, we explored the efficacy of DCs loaded with exosomes derived from CSC‐enriched colonospheres (CSCenr ‐EXOs) as an antigen source in activating CSC‐specific T‐cell responses. HT‐29 lysate, HT‐29‐EXOs and CSCenr lysate were independently assessed as separate antigen sources. Having confirmed CSCs enrichment in spheroids, CSCenr ‐EXOs were purified and characterized, and their impact on DC maturation was investigated. Finally, the impact of the antigen‐pulsed DCs on the proliferation rate and also spheroid destructive capacity of autologous T cells was assessed. CSCenr ‐EXOs similar to other antigen groups had no suppressive/negative impacts on phenotypic maturation of DCs as judged by the expression level of costimulatory molecules. Notably, similar to CSCenr lysate, CSCenr ‐EXOs significantly increased the IL‐12/IL‐10 ratio in supernatants of mature DCs. CSCenr ‐EXO‐loaded DCs effectively promoted T‐cell proliferation. Importantly, T cells stimulated with CSCenr ‐EXOs disrupted spheroids' structure. Thus, CSCenr ‐EXOs present a novel and promising antigen source that in combination with conventional tumour bulk‐derived antigens should be further explored in pre‐clinical immunotherapeutic settings for the efficacy in hampering recurrence and metastatic spread.